Quantum Interference in Wilkinson Power Dividers. Issue 8 (3rd July 2022) - Hernández, Osmery; Ortega‐Gomez, Angel; Bravo, Mikel; Liberal, Iñigo
Abstract: Scaling up quantum technologies entails the challenge of developing large‐scale and high‐performance photonic quantum networks. Engineering novel optical components, with a compact footprint and advanced functionalities, might help addressing this challenge by reducing the size and complexity of optical networks. Here, quantum interference phenomena in Wilkinson power dividers (WPDs), a popular element of microwave networks, is investigated. It is theoretically demonstrated that WPDs grant access to coherent perfect absorption (CPA) quantum state transformations (single photon CPA, coherent absorption of N00N states, two‐photon nonlinear absorption, and absorption of coherence in squeezed light) in CPA networks with a smaller footprint and a reduced number of elements. Additionally, it is shown how a WPD can be designed in a pure silicon‐on‐insulator platform by taking advantage of radiative losses. These findings might represent an important step forward in the development of CPA quantum networks. Abstract : The Wilkinson power divider (WPD) is presented as a novel device for quantum interference applications, leading to quantum networks with a smaller footprint and a reduced number of elements. Specifically, coherent perfect absorption quantum state transformations are theoretically demonstrated for a WPD. By harnessing radiative losses, an implementation of the device in a pure silicon‐on‐insulator platform is proposed.